Unbounded Personal Jurisdiction Theory and Foreign Policy Concerns: A Continental View on Fuld v. Palestine Liberation Organization - Dominelli, Stefano (CUADERNOS DE DERECHO TRANSNACIONAL, 2026)
The work critically analyses a recent judgment by the US Supreme Court which has clearly interpreted for the first time the due process limits under the Fifth Amendment. By exploring the solution adopted by the court on federal personal jurisdiction in terrorism related claims against out ofState defendants, from a continental point of view, it is argued that the judgment reinforces the Lotus principle on territorial adjudicative jurisdiction and constitutes and index that heads of jurisdiction may be justified even when there is little objective connection, but a strong policy interest. Assuming that for some States, policy-oriented heads of jurisdiction express the vision that adjudicative jurisdiction remains a legitimate tool to enforce public policies, the contribution highlights that the subsequent question of the free movement of the decision will impose a moment of reflection on extra-territorial prescriptive and adjudicative jurisdiction